Bimbingan Skripsi Daring Selama Pademi COVID-19 pada Mahasiswa PGSD UWKS : Hambatan dan Solusi - Kintama, Arvio Yosie; Larasati, Diyas Age; Yuliana, Leni (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2021)
abstractBased on this reseach, the aim is to find out the obstacles and solutions from online thesis guidance during the COVID-19 pandemic in PGSD UWKS students. This reseach method uses descriptive qualitative reseach instrument namely questionnaire. The subject of this study were USD students who took part in the thesis course in 2019 with a total of 20 students. This reseach method uses descriptive qualitative method by asking 17 questions to 20 PGSD UWKS students. Based on the results of the study there were 81% of 19 PGSD UWKS students less effective consulting using this online method. Obstacles in this reseach such as by using online methods students do not understand the material / delivered by lectures, especially students who carry out online consultations. The solution to the previous problem is that students more intensely communicative eith the supervisor using / combining several more supportive apllications such as whatsapp, zoom, skype, teams, email, for the achievement of thesis consultation achievement.Keyword : Thesis, Online, Obstacles and Solutions.Â